Mystery history of a pirate galleon - Finney, Fred; Bell, Mike; Berridge, Richard; Hutchins, Roger (Brookfield, Conn. : Copper Beech Books, 1996)
Describes life aboard a pirate ship. Includes games, puzzles, and mazes.
Includes index.
Keywords: Pirates -- Juvenile literature; Galleons -- Juvenile literature; Pirates